Exploring the supportive care needs of families affected by pancreatic cancer: a mixed-methods study protocol - Tara Anderson; Gillian Prue; Lisa Graham-Wisener; Susan McLaughlin; Gary Mitchell (BMC Cancer)
Abstract Background Pancreatic cancer is an aggressive disease with most cases diagnosed at an advanced stage resulting in low survival rates. Family members often take on a role of supporting patients’ needs. Families tend to be unprepared for this and experience high levels of unmet needs and substantial impacts to their own wellbeing, heightened by the rapid deterioration and short life expectancy associated with pancreatic cancer. Aim The proposed study aims to explore the supportive care needs and associated psychosocial impact of pancreatic cancer on family members, and the role of support services in supporting these families. Methods A sequential explanatory mixed methods design will be utilised. Data collection will consist of three phases: (1) Survey of affected family members to explore their supportive care needs and psychological wellbeing; (2) Semi-structured interviews to explore the lived experiences of family members across the disease trajectory, their psychosocial adjustment, and their perceptions of support services; (3) Focus groups with support services providers to explore their experiences in providing support to affected families. Discussion By combining quantitative and qualitative approaches, this research aims to provide a comprehensive understanding of the challenges and opportunities in providing psychosocial support to families affected by pancreatic cancer, ultimately enhancing their quality of life during and after the cancer journey. The findings may help to inform the development and enhancement of support programs, tailored to meet the specific needs of affected families.